PENGARUH KOMUNIKASI, PELATIHAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI BADAN NARKOTIKA NASIONAL PROVINSI BENGKULU MENURUT PRESPEKTIF ISLAM - RATIH KOMALA DEWI (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2019)
This study describes the influence of communication, training, and motivation on employee performance in the Bengkulu Province National Narcotics Agency. The method of data collection in research subjects was determined using purposive sampling, namely all employees of the National Narcotics Agency of Bengkulu Province 64 people who were respondents in. The qualitative method of data analysis is done by processing SPSS 17 software data with F test statistics and t test statistics and drawing conclusions and verifying data. The results of this study indicate that communication, training and motivation have a simultaneously significant influence on the performance of the Bengkulu Province National Narcotics Agency. At the Bengkulu Provincial Narcotics Agency, communication as a medium for delivering information is very important to support the task of the National Narcotics Agency as a vocal point to make efforts to prevent, eradicate the use and illicit circulation of drugs. In addition, the training provided by the Bengkulu Province National Narcotics Agency greatly supports improved performance so that employees can work more optimally. Furthermore, the motivation given by superiors to employees of the Bengkulu Provincial Narcotics Agency also had a positive impact on employee performance.